Swallowed danger: A Case Report of Accidental Acid Ingestion in a Child - Roopeshwar .; Mahesh Meena (Asia Pacific Journal of Medical Toxicology)
Introduction: Accidental acid ingestion in children is a severe yet preventable emergency, often leading to fatal complications. It is more common in regions where acids are easily accessible due to inadequate safety regulations and improper storage. Such incidents can cause extensive gastrointestinal and systemic damage, requiring immediate medical intervention.Case Presentation: A 6-year-old boy accidentally ingested acid at home, leading to severe vomiting, respiratory distress, and extreme pain. He was rushed to the hospital in critical condition, where initial stabilization attempts were administered, which included intravenous fluids, pain management, and proton pump inhibitors. Despite aggressive medical intervention, his condition rapidly deteriorated, and he succumbed within 18 hours. Autopsy findings revealed extensive esophageal charring, gastric perforation, and severe tissue necrosis, indicative of widespread corrosive damage.Discussion: Accidental ingestion of corrosive acids, particularly among children, remains a serious public health concern. Studies indicate that nearly 80% of such cases involve children, with most incidents occurring at home due to poorly stored household cleaners or industrial chemicals. Unlike adults, where acid ingestion is often intentional and more severe, pediatric cases are accidental but still carry significant risks. Even small amounts of corrosive substances can lead to damaging effects, including gastrointestinal burns, perforation, hemorrhage, infection, sepsis, and death. Immediate endoscopic evaluation is crucial for assessing damage.Conclusion: This tragic case underscores the urgent need for stronger preventive measures. Implementing stringent regulations, increasing caregiver awareness, promoting childproof storage solutions, and enforcing proper labeling of hazardous substances can significantly reduce such incidents and protect children from life-threatening injuries.